Histological aberrations and mode of damage of cowpea (Vigna unguiculata) by Colletotrichum destructivum - David Nwazuo Enyiukwu; ANDERSON CHIDI AMADIOHA; CHARLES CHIMEZIE ONONUJU (Nusantara Bioscience, 2021)
Abstract. Enyiukwu DN, Amadioha AC, Ononuju CC. 2021. Histological aberrations and mode of damage of cowpea (Vigna unguiculata) by Colletotrichum destructivum. Nusantara Bioscience 13: 16-23. Leaf and stem of healthy 2-week old cowpea (Vigna unguiculata L. Walp.) seedlings were inoculated with spore suspension of the Colletotrichum destructivum O’Gara. Sections of the infection courts were prepared and examined under digital microscope. The results showed that the infection process began 12 hours after inoculation (hai) with the germination of spores of the fungus. Large multi-lobed primary hypha (somewhat spherical in shape) developed from the infection peg and remained inside a single epithelial cell for about 3 days. Towards the end of this time, the primary hyphae developed thin filamentous tentacles that punctured and branched into adjoining cells, initiating necrotrophic phase of the disease. During this period, typical anthracnose symptoms began to develop on the infected organs of the crop. The entire infection process lasted a maximum of 96 h, at the end of which acervulus that bore a single seta emerged on infected crop lesions. The mechanism of damage of the pathogen involved intra-cellular and inter-cellular colonization of the host tissues early and late in the disease cycle. The integrity of the affected tissues' cells was compromised by passage and colonization of Colletotrichum destructivum O’Gara evidenced by lack of clear-cut middle lamella and cell boundaries. Anthracnose affected cells dispossessed of vital nutrients became turbid, devoid of turgidity and vigor. Thus, these results have strong implications for plant health management in that effective environment-compliant control of the fungus should be initiated on or before the third day following arrival of the conidia of the pathogen on the crop. Seeds are major agents of introduction of Colletotrichum spp. to disease-free locations. Findings from this study also support that strong trans-border control of seeds of the crop should be maintained since the pathogen is known to be seed-borne and demonstrates sufficient cross-infection of crop plants. Key words: Hemibiotrophy,  Colletotrichum destructivum, Anthracnose, Cowpea,  Hyphal colonization